Trainability of sprinting in youth male and female soccer players - Mathisen, G. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Sprinting and change of direction sprints (agility) is important for youth soccer players. Compared to adult athletes there is less information about the effectiveness of sprint training in youths. The aim of the present study was to examine the trainability of sprint and agility performance in male and female youth soccer players. Method: This present study is a collection of four intervention programs, with 10 to 13 year-old boys, and 13 to 15 years-old girls. In total, 57 subjects (34 boys and 23 girls participated in the intervention programs. The training sessions involved running in short burst with starting, stopping, change of direction, and linear sprints, all executed with maximal effort. Control groups followed ordinary soccer training sessions. The sprint test consisted of 20 m straight-line course, and the agility (change of direction sprint) test was a 20 m standardized course with 90° and 180° turns. Electronic timing gates, wireless connected with a timer was used to record the times (Brower Timing System, US). Results: Training groups showed significant improvement in 20 m sprint (p<0.05): 10.5 (±0.2) year old boys 20 m from 3.96 (±0.24) to 3.89 (±0.21); 13.5 (±0.2) year old boys; from 3.54 (±0.17) to 3.42 (±0.18); 13.6 (±0.2) years-old girls; from 3.75 (±0.15) to 3.62 (±0.22), 15.5 (±0.7) year old girls from 3.53 (±0.15) to 3.42 (±0.16). Training groups showed significant improvement in agility performance (p<0.05): 10 year-old boys from 9.15 (±0.57) to 8.42 (±0.39), 13-years-old boys from 8.23 (±0.34) to 7.69 (±0.34), 13 years-old girls from 8.56 (±0.54) to 8.03 (±0.38), 15 year-old girls from 8.23 (±0.31) to 7.80 (±0.33). Discussion: Faster completion of sprinting indicates that the intervention programs consisting of short burst highspeed exercises is effective in youth soccer players. The results are in line with pervious findings with youth athletes, showing improved sprint performance with high-intensity speed training, and programs that are specific to the performance tests. The improvement is supposed to be due to that neuromuscular adaptions including recruitment, activation of motor units and better coordination of muscles have occurred.